Perbandingan Hasil Uji Schirmer Test I Sebelum dan Sesudah 2 jam Menggunakan Komputer pada Mahasiswa di Universitas Komputer Indonesia - Witjaksono, Arief; Carolina, Anisa (stikes dharma husada bandung, 2021)
A decrease in the number of flashing reflexes plays a role in the low production of tears and temporarily stresses the cornea and results in dry eyes. To reduce the possibility of dry eyes when using a computer, it is recommended to blink more often to maintain ocular surface moisture. Imperfect flashing reflexes are also found in computer users which also have an impact on tear stability. The purpose of this study was to determine the differences in the results of the Schirmer test I test before and after 2 hours of computer use. This type of research with Pre and Post before and after 2 hours using a computer cross-sectional method with the research method using purposive sampling with the Wilcoxon Test calculation method. This study used the Schirmer Test and Observational Sheet. The results showed that 23 people (76.7%) after 2 hours using computers were categorized as experiencing Non Dry Eye, then as many as 3 people (10.0%) were categorized as having mild dry eye and 7 people (13.3%) categorized as moderate dry eye from the number of samples 30 people. There are differences before and after using a computer (p = 0.03). It is recommended that you do not use the computer at rest time to rest your eyes, adjust the brightness of the computer, and adjust the visibility to the screen.